Unsettling relations: Disrupting the ethical subject in fan studies research. (1st September 2016) - Whiteman, Natasha
This article takes as its focus the strategies by which ethical stances are established and legitimized in fan studies writing. It argues that, as a matter of ethics, such stances should always be placed under interrogation. This can be achieved by disrupting the entities that are often invoked in claims about what constitutes ethical practice in research – ones that may otherwise quickly become naturalized points of reference. Using as an exemplar Busse and Hellekson's articulation of the 'fans first' principle, the article considers how ethical positions become sedimented and normalized within academic fields of practice. In doing so, the article develops some counter-principles for an ethical destabilization and (where necessary) dismantling of received ethical subjectivities in fan studies research.